Perancangan Knowledge Management System Dalam Meningkatkan Kemampuan Pemanfaatan Teknologi Pada Pembelajaran - Dwiyatno, Saleh; Sulistiyono, Sulistiyono; Jubaedi, Ahmad Dedi; Krisnaningsih, Erni; Rakhmat, Edy (Teknik Informatika Fakultas Ilmu Komputer, 2023)
Knowledge management systems in educational institutions are implemented as a form of increasing and utilizing resources and technology as knowledge assets in increasing competitive advantage. The ability of an educational institution regarding technology is a very important factor for the progress and development of the educational institution. At SDN Gelam 3, Serang City, the system should have been developed by utilizing technology. This is because, the problem that often occurs at SDN Gelam 3 Serang City is the lack of knowledge and ability to use technology, such as at the beginning of a new school year, each teacher collects learning outcomes in hardcopy form to the school administrator so that mistakes and lost files often occur. And besides that, there are differences in teaching materials between one teacher and another teacher. Through this research, researchers help build a knowledge management system by utilizing technology in the form of a website. This system will be created in the form of a website using the programming language PHP and MySQL as database management. And researchers did system design in the form of UML diagrams, user interfaces and databases. The results achieved are in the form of designing a knowledge management system that can support increasing the utilization of technological capabilities in learning